2012
DOI: 10.1007/s11284-012-1007-8
|View full text |Cite
|
Sign up to set email alerts
|

Among‐population variation in resistance traits of a nettle and its relationship with deer habitat use frequency

Abstract: Because leaf hairs serve as resistance against herbivores, among‐population variation in hair production may arise from adaptation to local herbivore communities. It is possible that Japanese nettle (Urtica thunbergiana) shows among‐population variation in stinging hair abundance that is associated with the frequency of habitat use by sika deer (Cervus nippon). We examined 31–32 individuals of each of 19 populations for leaf area, stinging hair number (/leaf) and stinging hair density (per square centimeter) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(45 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…These results confirm the hypothesis that nettles with high stinging-hair densities in Nara Park evolved under natural selection imposed by intense deer browsing, as previous studies suggested (Pollard and Briggs 1982, 1984a, b, Pullin and Gilbert 1989, Tuberville et al 1996, Kato et al 2007, Shikata et al 2013. Dense stinging hairs were found along the stems as well as on leaves in nettles of Nara Park (data not shown), preventing the whole plant from being consumed by the ungulate.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These results confirm the hypothesis that nettles with high stinging-hair densities in Nara Park evolved under natural selection imposed by intense deer browsing, as previous studies suggested (Pollard and Briggs 1982, 1984a, b, Pullin and Gilbert 1989, Tuberville et al 1996, Kato et al 2007, Shikata et al 2013. Dense stinging hairs were found along the stems as well as on leaves in nettles of Nara Park (data not shown), preventing the whole plant from being consumed by the ungulate.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous studies supported the hypothesis that a much higher density of stinging hairs on nettles of Nara Park had evolved as a defense against sika deer (Kato et al 2007;Shikata et al 2013). To confirm this hypothesis, we needed to address at least two problems: whether stinging hairs serve as defenses against insect herbivores and the degree to which stinging hairs deter sika deer.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…, Shikata et al. ). Such change in the hair density could impact the preference or performance of other animals feeding on the same nettles.…”
Section: Introductionmentioning
confidence: 99%